2019
DOI: 10.1016/j.jgr.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Trichoderma citrinoviride isolated from mountain-cultivated ginseng (Panax ginseng) has great potential as a biocontrol agent against ginseng pathogens

Abstract: Background Ginseng ( Panax ginseng Meyer) is an invaluable medicinal plant containing various bioactive metabolites (e.g., ginsenosides). Owing to its long cultivation period, ginseng is vulnerable to various biotic constraints. Biological control using endophytes is an important alternative to chemical control. Methods In this study, endophytic Trichoderma citrinoviride PG87, isolated from mountain-cultivated ginsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Generally, secondary metabolites synthesized by the BEs help the host plants fight and protect against the pathogens 22 or from any abiotic stress 23 . Several antimicrobial 13 , antifungal 11 and antinematicidal 24 activities of such secondary metabolites have been well documented 25 . Due to existing evidence of these inhibitory abilities, we investigated the antinematicidal activity of diverse BEs isolated from the four Pinus species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, secondary metabolites synthesized by the BEs help the host plants fight and protect against the pathogens 22 or from any abiotic stress 23 . Several antimicrobial 13 , antifungal 11 and antinematicidal 24 activities of such secondary metabolites have been well documented 25 . Due to existing evidence of these inhibitory abilities, we investigated the antinematicidal activity of diverse BEs isolated from the four Pinus species.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies focusing on the use of BEs as biocontrol agents have shown a promising glimpse of their remedial application in the agriculture sector 10 . In general, BEs colonizing host plants have the tendency to demonstrate antagonistic activity against their own or different plant pathogens 11,12 . These beneficial activities are due to the production of secondary metabolites by BEs, many of which are used for various applications 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these traits predicted the outcome of a three-partite interaction among a host, a pathogen, and an endophyte mutualist. Various Trichoderma species and strains isolated as endophytes and characterized as having mycotrophic traits in vitro (dual assays) were later inoculated into host plants, successfully reducing the presence of a fungal plant pathogen and consequently reducing and/or preventing disease in the host (Pujade-Renaud et al (2019); Lahlali & Hijri, 2010;Park et al, 2019). As fungal traits are measured in the laboratory and tested in the field, their utility can be increased by documenting experimental conditions and cataloguing fungal strains for future.…”
Section: Size-related Scalingmentioning
confidence: 99%
“…T. reesei is a well-studied saprobe and used industrially for the production of cellulases and hemicellulases [12]. T. harzianum is a ubiquitous species with agricultural applications, the opportunistically pathogenic T. citrinoviride is often isolated as endophyte and T. brevicompactum is a producer of antifungal metabolites [12,[19][20][21]. All mentioned Trichoderma species contain various classes of BGCs, Type 1 polyketide synthetases (T1pks), nonribosomal peptide synthases (NRPSs), terpene BGCs, fatty acid BGCs and various combined and putative clusters.…”
Section: Introductionmentioning
confidence: 99%